Brain Drain Competition Policies in Europe: a Survey - Pierpaolo Giannoccolo (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2005)
To obtain the "1.2 million additional research personnel, including 700.000 additional researchers" necessary to "irrigate" the industries science-based, the EU stresses that it is not sufficient increase the investment in Research. We have to stop the European Brain Drain. We have to reverse it; "Europeans who have moved abroad would love to come home". We have to remember that the "B rain Drain should work in both directions", then we have to attract foreign brilliant scientists and compete to the USA. In this paper we give a survey of the principal "Brain Drain Competition" policies implemented in Europe. The key strategies and mechanisms found are: making the academic system more open and flexible; improving the regulatory conditions particularly on immigration; better sign-posting and information at national level; dedicated grants for foreign researchers; adapting income situations to market forces; providing tax reductions specifically for researchers and knowledge workers; more active international marketing and support for international researchers. Finally, we analyse the effects of these policies on the Brain Drain in Europe by giving examples of countries (i.e. UK, France, Germany, Belgium, etc) that that effectively reverse the Brain Drain and attract foreign researchers, and the exemplum of the Italy that it is "a countries that supplies talent to Europe and the Americas".
Keywords: 330; Brain Drain; Migrationspolitik; Humankapital; EU-Staaten